P1125 Safety and efficacy of ventricular tachycardia ablation during sinus rhythm in patients with structural heart disease. (18th June 2020) - Fernandez-Armenta Pastor, J; Silva, E; Soto-Iglesias, D; Penela, D; Acosta, J; Jauregui, B; Bisbal, F; Linhart, M; Fernandez, M; Borras, R; Villuendas, R; Cano, L; et al.
Abstract: Funding Acknowledgements: Project "PI-0057-2017", funded by Junta de Andalucía and co-funded by European Union (ERDF/ESF, "Invesing in your future") Background: The best strategy for scar related ventricular tachycardia (VT) ablation is not yet established. Recently, the use of ventricular assist devices is being proposed to allow ablation during unstable VT.  Purpose: Analyze the results of a multicenter registry of substrate-guided VT ablation performed primarily during stable rhythm. Methods   This prospective multicenter registry included 433 VT ablation procedures performed in 372 consecutive patients with structural heart disease undergoing VT ablation. Substrate ablation (scar dechanneling technique) during sinus rhythm without initial VT induction was the standard protocol. Any episode of sustained VT or appropriate ICD therapy was considered VT recurrence.  Results   Myocardial infarction was the arrhythmogenic substrate in 64% of patients. 90.5% of patients were male, mean age 64 ± 13 years. Mean LVEF was 38 ± 13%.No ventricular assist device was used in any case. After substrate ablation no VT was inducible in 69% of cases. End-procedure non-inducibility was achieved in 73.1% of cases. Complication rate was 6.7 %. 30-days mortality was 1.9% (7 patients), including one procedure related death. At one year after first procedure 17 patients died (4.5%). Age, chronic obstructive pulmonary disease and renal failure were independent predictors of mortality. One-year freedom from VT recurrence was 84%.  Conclusion: Substrate-guided VT ablation during stable rhythm as main approach for scar-related VT treatment is associated to low complication and recurrence rates in this prospective multicenter study.